2018
DOI: 10.3389/fnins.2018.00813
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor as a Central Regulator of Metabolism – Implications for the Development of Obesity

Abstract: The hypothalamus plays a major role in the regulation of food intake and energy expenditure. In the last decade, it was demonstrated that consumption of high-fat diets triggers the activation of an inflammatory process in the hypothalamus, inducing neurofunctional alterations and contributing to the development of obesity. Hypoxia-inducible factors (HIFs) are key molecules that regulate cellular responses to inflammation and hypoxia, being essential for the normal cell function and survival. Currently, evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 134 publications
4
45
0
2
Order By: Relevance
“…This interplay is further evidence of hypoxia and the AR controlling a metabolic switch that promotes CRPC development (Geng et al 2018). HIF itself plays a central metabolic role evidenced by an overexpression of both HIF1α and HIF2α in the hypothalamus involved in both weight gain functions, glucose uptake and energy expenditure (Gaspar & Velloso 2018). HIFs are also involved in lipid metabolism, as uptake of extracellular fatty acids and triglyceride synthesis are upregulated during hypoxia through PPARg activated by HIF1 which additionally mediates the expression of FABP3 and FABP4 in tumour cells (Mylonis et al 2019).…”
Section: Other Drivers Of Crpc Include Cytoskeletal Ar/upr-related Chmentioning
confidence: 76%
“…This interplay is further evidence of hypoxia and the AR controlling a metabolic switch that promotes CRPC development (Geng et al 2018). HIF itself plays a central metabolic role evidenced by an overexpression of both HIF1α and HIF2α in the hypothalamus involved in both weight gain functions, glucose uptake and energy expenditure (Gaspar & Velloso 2018). HIFs are also involved in lipid metabolism, as uptake of extracellular fatty acids and triglyceride synthesis are upregulated during hypoxia through PPARg activated by HIF1 which additionally mediates the expression of FABP3 and FABP4 in tumour cells (Mylonis et al 2019).…”
Section: Other Drivers Of Crpc Include Cytoskeletal Ar/upr-related Chmentioning
confidence: 76%
“…Hypoxia-inducible factors are key molecules that regulate the cellular response to hypoxia and inflammation and play a major role in normal cell function and survival [49]. Current evidence also indicates that the HIF-1α pathway in the hypothalamus may be involved in the regulation of food intake and energy expenditure [49].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-inducible factors are key molecules that regulate the cellular response to hypoxia and inflammation and play a major role in normal cell function and survival [49]. Current evidence also indicates that the HIF-1α pathway in the hypothalamus may be involved in the regulation of food intake and energy expenditure [49]. Previous studies have shown that 30 cycles of intermittent hypoxia per hour for 8 hours per day for 21 days reduces body weight and BAT wet weight in rats [50].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with reports that proliferating hMSCs have a glycolytic phenotype, undifferentiated cells have high levels of hypoxia-inducible factor 1 (HIF-1), a transcriptional regulator central to regulation of genes that are involved in hypoxic responses. It is also a crucial physiological regulator of anaerobic metabolism (Gaspar and Velloso, 2018). Cells undergoing OD downregulate HIF-1.…”
Section: Metabolism Of Mscs Msc Function Is Linked To Metabolismmentioning
confidence: 99%